Brain responses to uncertainty about upcoming rectal discomfort in quiescent Crohn's disease – a fMRI study. Issue 9 (2nd May 2016) - Rubio, A.; Pellissier, S.; Van Oudenhove, L.; Ly, H. G.; Dupont, P.; Tack, J.; Dantzer, C.; Delon‐Martin, C.; Bonaz, B.
Abstract: Background: Patients with Crohn's disease (CD) in remission are exposed to chronic psychological distress, due to the constant risk of relapse. This permanent situation of anticipation and uncertainty can lead to anxiety, which may, in turn, trigger relapse. We aimed to investigate the effects of uncertainty on behavioral and brain responses to anticipation of visceral discomfort in quiescent CD patients. Methods: Barostat‐controlled rectal distensions were preceded by cued uncertain or certain anticipation in nine CD patients and nine matched healthy volunteers. Brain responses obtained before distension across the different anticipation conditions in regions of interest (ROI) involved in (anticipation of) pain were measured using functional magnetic resonance imaging and compared between CD and controls. The association between anxiety‐related psychological variables and cerebral anticipatory activity was tested. Key Results: During uncertainty, CD patients had significantly stronger activations than controls in the cingulate cortex, insula, amygdala, and thalamus with trends in the hippocampus, prefrontal, and secondary somatosensory cortex. In patients, brain responses to uncertainty in the majority of ROI correlated positively with gastrointestinal symptom‐specific anxiety, trait‐anxiety, and intolerance of uncertainty. Conclusions & Inferences: In a context of uncertainty regarding occurrence of uncomfortable visceral sensations, CD is associated with excessive reactivity in brain regions known to be involved in sensory, cognitive and emotional aspects of pain processing and modulation, and threat appraisal. Our findings contribute to a better understanding of the role of emotional and cognitive processes in CD. This may, in turn, lead to the development of new (psycho)therapeutic approaches for management of symptoms and related anxiety. Abstract : During uncertainty regarding the occurrence of visceral discomfort, CD patients have significantly stronger activations than controls in brain regions implicated in sensory, cognitive and emotional aspects of pain and threat appraisal, and in autonomic responses. These brain responses to uncertainty correlate positively with gastrointestinal symptom‐specific anxiety, trait‐anxiety, and intolerance of uncertainty.